Disinfection by 1% sodium hypochlorite through cold fogging: an innovative appropriate technology against COVID-19 in public health - Gupta, Arun; Kaushik, S. K.; Kapoor, Suraj; Sabarwal, Gurmesh S.; Bobdey, Saurabh; Singh, Kamalpreet (International Journal of Research in Medical Sciences, 2021)
Background: SARS-CoV-2 is an enveloped virus with a fragile outer lipid envelope that makes it more susceptible to disinfectants compared to non-enveloped viruses. In this article, dispensation through cold Fogger was innovated as a measure against aerosol-based transmission of COVID-19 in large, enclosed spaces like hospitals, nursing homes, isolation centers and quarantine facilities. Methods: Ecological exploratory study, to ours effectiveness of 1% sodium hypochlorite through cold fogging against SARS COV-2 technology. Study setting included medical college in Western Maharashtra and the selected COVID-19 hospitals. The data was collated in MS excel and analysed using IBM SPSS version 23.0. Results: Average of 2.9 % HCWs got infected in hospitals where this innovation was used to disinfect, as compared to infections rates of 21.5% and 14.7% in other premier health institutes. There was strong negative correlation between percentage of health care infected and liters of sodium hypochlorite used with R2=0.56. Also, on applying Spearman correlation coefficient there was good negative correlation (-0.8). Conclusions: This appropriate technology has shown significant reduction in infection, with antecedent benefit of decreased morbidity and mortality of precious trained manpower. It gives much better dis-infection at 07 times less the cost and can be conveniently used for dis-infection against COVID-19 at the very periphery of primary health care delivery done at Sub-centres and PHCs.